From care packages to Zoom cookery classes: youth work during the COVID-19 "lockdown". Issue 1 (10th March 2022) - Shaw, Aileen; Brady, Bernadine; Dolan, Patrick
Abstract : Purpose: This paper aims to explore the experience of one large Irish youth work organisation, Foróige, to measures introduced during the initial phase of COVID-19 in 2020. In the face of the unprecedented crisis including the closure of schools and curtailment of many youth services, this paper examines how the organisation responded and adapted its service offering. Design/methodology/approach: Qualitative semi-structured interviews were conducted with 12 senior managers and youth officers in Foróige to explore their perspectives on the organisation's response. Participants were purposively sampled from across the operational management functions and also from regional levels and youth workers engaging in work "on the ground". Findings: Shifting from a face-to -face, relationship-based to a distanced mode of engagement with young people, colleagues and volunteers required significant adaptation of Foróige's service model. Innovation took place both in the delivery platform and fundamentally, in its service orientation. The accelerated move to online youth work brought about by the pandemic enabled the organisation to embrace and learn from the challenges and opportunities posed by digital technology. Responding to the immediate and tangible needs of young people in receipt of services, staff found themselves working with families at the more basic levels of intervention. Originality/value: This paper provides new insights into the nature of non-profit service innovation during a time of unprecedented crisis management. It highlights characteristics of organisational agility that can assist organisations in managing crises, while also pointing the way towards a more flexible operating model for youth work service delivery.